The Effect of American Civil War to Scarlet's Love Manifestations as Seen in Margaret Mitchell's Gone With The Wind - Reni Zilfiameri; Helmita Helmita (Fakultas Sastra Universitas Ekasakti, 2019)
This research is a study about Scarlet’s marriage from the novel Gone with the Wind and the history American Civil War. Scarlet’s love has changed from romantic love to materialistic love before and after the war. The purpose of this study is (1) to analyzed the effect of American Civil War on Scarlet’s first marriage to Charles Hamilton (2) to analyzed the effect of American Civil War on Scarlet’s second marriage to Frank Kennedy (3) and to explain the effect of American Civil War on Scarlet’s third marriage to Rhett Butler. The approach used is a psychological approach that the discusses the overall analysis in literature, both in extrinsic and intrinsic. The theory used in this research are the theory psychological and historical of literature according to Alan Daiches and Russel which states reflection of the characters’ psychological behavior in life and remembering the moment/historic moment a long with the literary work written. This study employs the qualitative method. The object of the study is focuses on the central figure of a Southern woman named, Scarlett O’Hara play written by Margaret Munnerlyn Mitchell. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the play script itself and the secondary data sources are script text and some references related to the research. The technique of the data collection is note-taking. The technique of the data analysis are telling and showing method. The first, previous to the war, when everything is peaceful and prosperous, Scarlet marries because of her feeling to Charles Hamilton. Ashley’s marriage to Melanie Hamilton and rejection of Scarlet drive nearly all of Scarlet’s important subsequent decisions. Scarlett marries Charles Hamilton to hurt Ashley. After the war when everything is destroyed and poor condition, Scarlet marries because of her need on money to pay the tax and develop her business.